Beyond trading: Knowledge spillovers and learning-by-exporting in global value chains - Holger Graf; Hoda Mohamed (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2023)
Does exporting intermediate goods induce learning from importers? In this paper, we examine to what extent learning from German industries can be explained by knowledge spillovers, channeled through the export of intermediate goods. Our study is based on a sample of 27 German trade partners in 14 manufacturing industries for the period 2004 to 2016. Using data on patent citations and trading in intermediate goods, we find support for the widely known 'learning-by-exporting' hypothesis. Our analyses reveal that citations to German patents are positively related to exported intermediate goods weighted by German R&D expenditure. The relationship between these spillovers and learning seems to be particularly strong in certain industries. We also show that the level of absorptive capacity of the exporting trade partner, as measured by the number of researchers involved in R&D activities, plays a role in mediating these spillovers.
Keywords: F14; O14; O32; O33; 330; GVC; trade; intermediate goods; learning-by-exporting; knowledge spillovers